Pengaruh Lingkungan Kerja Fisik dan K3 (Keselamatan dan Kesehatan Kerja) terhadap Risiko Kecelakaan Kerja di Perkebunan Kelapa Sawit : Studi Kasus di PTPN III Kebun Cikasungka Pabrik Kelapa Sawit 2 Cigudeg, Bogor - Anggi Nopita Firmansyah; Risza Putri Elburdah (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This research aims to determine the effect of the physical work environment and Occupational Safety and Health (K3) on the risk of work accidents among employees of PTPN III Kebun Cikasungka Pabrik Kelapa Sawit 2 Cigudeg Bogor. The research method used is associative quantitative with a survey technique through the distribution of questionnaires to 77 respondents. Data analysis was conducted using multiple linear regression with SPSS version 22. The results show that the physical work environment has a positive and significant effect on the risk of work accidents (tcount 5.893 > ttable 1.993; sig. 0.000 < 0.05). Occupational Safety and Health (K3) also has a positive and significant effect on the risk of work accidents (tcount 14.086 > ttable 1.993; sig. 0.000 < 0.05). Simultaneously, both variables significantly influence the risk of work accidents (Fcount 98.213 > Ftable 3.120; sig. 0.001 < 0.05), with a coefficient of determination (R²) of 0.726. This indicates that 72.6% of the variation in the risk of work accidents can be explained by the physical work environment and Occupational Safety and Health (K3), while the remaining 27.4% is influenced by other factors outside this research. Thus, the better the physical work environment conditions—including lighting, air circulation, cleanliness, and equipment layout—and the more optimal the implementation of Occupational Safety and Health (K3) through the use of personal protective equipment (PPE), K3 training, and supervision of procedures, the lower the risk of work accidents will be. Therefore, the company is advised to improve the quality of the physical work environment and strengthen the implementation of Occupational Safety and Health (K3) standards to create a safe, productive, and sustainable work environment.